HISTOLOGICAL OBSERVATIONS ON THE MIDGUT AND HINDGUT OF MACROBRACHIUM MALCOLMSONII (CRUSTACEA : DECAPODA) - ., LALITHA; VIJAYALAKSHMI, C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
The morphology and histology of the midgut and hindgut in the freshwater prawn Macrobrachium malcalmsonii are described. The functional significance of these structures is discussed.